The Impact of Early Marriage from the Perspective of Child Protection Law on Stunting Prevention (Case Study in Ranah Batahan District, West Pasaman Regency) - Umam Lubis, Khairul; Hasanah, Uswatun (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Nowadays, early marriage often occurs in every sub-district with various causal factors, even though the age of marriage is regulated in Law Number 16 of 2019 in Article 7 which states that marriage is only permitted for men and women who have reached the age of 19 years. One of the sub-districts that practices early marriage is Ranah Batahan sub-district, West Pasaman district. The problem of the dangers of early marriage practices in Ranah Batahan sub-district, West Pasaman regency, has an impact on increasing cases of stunting in children. Early marriage is not only detrimental to children physically and mentally but is also contrary to the Child Protection Law Number 35 of 2014. This research is qualitative research using empirical juridical research methods which use two data sources, namely primary and secondary, with a different approach method. Used are field research and library research. The research results about the impact of early marriage on stunting prevention show the need for stricter law enforcement against the practice of early marriage in accordance with Article 66 of the Child Protection Law which stipulates that underage marriage is invalid. Public education is also important to increase awareness of children’s rights and encourage better social change. Protection of children suffering from stunting requires joint involvement from the state, community, family, and parents, by providing holistic legal, economic, social, and cultural protection. Thus, collaboration between stakeholders is key in ensuring optimal fulfillment of children’s basic rights